ELKO applications in cosmology - Pereira, S. H. [UNESP]; Pinho, A. S. S. [UNESP] (World Scientific Publ Co Pte Ltd, 2014)
A brief review is presented about the ELKO spinor field applied to cosmology, with the main results and limitations of the theory. As a simple application, we have analyzed a model involving the interaction of the ELKO spinor field with dark matter in the universe from a dynamical system approach. When the system is rewritten in terms of the deceleration parameter q and under the assumption that such parameter is nearly constant for some different stages of the evolution, stability points were found for different types of interaction between dark matter and ELKO spinors. Within this new analysis several interesting scenarios are possible, depending on the interaction term. For example, if it is assumed that the equation of the state parameter of the ELKO field is of the phantom type omega(phi) < -1, the current acceleration of the universe can be driven by the decay of dark matter particles into ELKO field. Furthermore, even for omega(phi) > 0, the inflationary period can be driven by the decay of the inflaton field (described by the ELKO spinor) into dark matter particles.
Keywords: ELKO spinors; Dark energy; Cosmology connection